Pretreatment Neutrophil-to-Lymphocyte Ratio Can Predict the Prognosis in Bladder Cancer Patients Who Receive Gemcitabine and Nedaplatin Therapy - Ohtake, Shinji (Biomed Res Int, 2016)
Introduction and Objectives. Neutrophil-to-lymphocyte ratio (NLR) has been suggested to be a simple marker of the systemic inflammatory response in critical care patients. We previously assessed the utility of NLR as a biomarker to predict tumor recurrence and cancer death in bladder cancer patients who underwent radical cystectomy. In this study, we evaluated the prognostic impact of NLR in bladder cancer patients who received gemcitabine and nedaplatin (GN) chemotherapy. Methods. A total of 23 patients who received GN chemotherapy for advanced bladder cancer were enrolled in this study. The cut-off point of NLR according to the sensitivity and specificity levels was derived from the area under receiver operator characteristics (AUROC) curve plotted for disease progression or overall mortality. Results. The NLR cut-off point was determined as 4.14 for both tumor progression and overall mortality. Median progression-free survival (PFS)/overall survival (OS) in the higher NLR group (NLR ≥ 4.14) and lower NLR group (NLR < 4.14) were 194/468 days versus 73/237 days, respectively. Kaplan-Meier analysis showed that higher NLR significantly correlated with poorer PFS (p = 0.011) and OS (p = 0.045). Conclusions. NLR may serve as a new biomarker to predict responses to GN-based chemotherapy in advanced bladder cancer patients and/or their prognosis.